1992
DOI: 10.1159/000186900
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccination in Dialysis Patients and Nutritional Status

Abstract: 35 dialysis patients underwent anti-HBV vaccination. We classified patients in responders or non-responders using an anti-HBs titer of 50 UI/l as the discriminating serum level and tried to assess whether the antibody response bears any relationship with the nutritional status. 26 patients (74%) reached the target atb titer, which was maintained during follow-up (average 360 UI/l). The weak response in the other 9, with values never exceeding 20 UI/l, was short-lived. Anthropometric and impedenziometric parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…A list of the 94 bibliographic references is available from the authors on request. Eleven papers [12,13,14,15,16,17,18,19,20,21,22], representing a total of 862 unique patients, were included in our meta-analysis. There was a 100% concordance between reviewers with respect to final inclusion and exclusion of studies reviewed based on the predefined inclusion and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of the 94 bibliographic references is available from the authors on request. Eleven papers [12,13,14,15,16,17,18,19,20,21,22], representing a total of 862 unique patients, were included in our meta-analysis. There was a 100% concordance between reviewers with respect to final inclusion and exclusion of studies reviewed based on the predefined inclusion and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…There was 1 randomized clinical trial [17 ]and 10 cohort studies, 2 prospective [16,19] and 2 retrospective [20,21]. The design of the study (prospective or retrospective) remained unclear in 5 studies [12,13,15,18,22]. Khan et al [14] collected prospectively data on HD and retrospectively on peritoneal dialysis (PD) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Concomitant infection with HCV has a negative influence on vaccination with recombinant HBsAg as well [8,19]. Malnutrition (determined by concentrations of albumin, pre-albumin, and pre-dialysis blood urea nitrogen) had a negative influence on vaccination with recombinant HBsAg [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the immune compromise conferred by uremia, a series of host factors may affect the responsiveness to HBV vaccine in the HD population: Nutritional status [94,95], diabetes mellitus [96], male sex [97], body weight [98], older age [99], blood transfusion history [100], serological positivity for HCV markers [101], HLA genetic heterogeneity [102][103][104] and impaired antigen receptor expression [105]. Paradoxically, some reports [99,106] observed that responder vaccinees have been on HD longer than nonresponders; patients who survive on HD for longer periods are generally healthier and may be better able to develop an antibody response.…”
Section: Hbv Vaccination In Dialysis: Short-term Studiesmentioning
confidence: 99%